Game-based Interactive Digital Module: Application to Announcement Materials in English Language Learning - Arafah Husna; Made Duananda Kartika Degeng; Yulias Prihatmoko (Teknologi Pendidikan ID, 2025)
This study aims to develop a game-based interactive digital module that is effective in helping students understand the material “announcement” in English learning. The game-based approach is expected to increase student engagement, interest in learning, and understanding of concepts. The research method used is Research and Development (R&D) with the stages of needs analysis, module design, expert validation, field trials, and evaluation. The results showed that this module can increase students' active participation in learning and can facilitate them in understanding the material. The findings support the application of technology and game-based learning media as an innovative solution in language education.